2022
DOI: 10.1021/acssuschemeng.2c01719
|View full text |Cite
|
Sign up to set email alerts
|

A Multilayer Transparent Bamboo with Good Optical Properties and UV Shielding Prepared by Different Lamination Methods

Abstract: Transparent bamboo (TB) is a new type of biomass and light-transmitting material. However, due to the high density of bamboo, it is arduous for polymers to impregnate the bamboo, and the thickness of bamboo becomes a key factor limiting the development of transparent bamboo. Here, inspired by plywood, we report a multilayer transparent bamboo (MLTB). The aim of this experiment is to study the performance of MLTB under different lamination methods, including the influence of the number of layers and lamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…A 6.23-mm-thick TBH showed a certain optical transmittance, with a maximum transmittance of 59.2%. In our previous study, the light transmittance of 2.9-mm-thick transparent bamboo designed by multilayer superimposition was 53.7% [ 46 ]. However, when the thickness of the TBH was doubled, the light transmittance also increased by 10%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 6.23-mm-thick TBH showed a certain optical transmittance, with a maximum transmittance of 59.2%. In our previous study, the light transmittance of 2.9-mm-thick transparent bamboo designed by multilayer superimposition was 53.7% [ 46 ]. However, when the thickness of the TBH was doubled, the light transmittance also increased by 10%.…”
Section: Resultsmentioning
confidence: 99%
“…It is also challenging to prepare transparent bamboo of a certain thickness. To improve the thickness of transparent bamboo than in our previous study, we prepared transparent bamboo through multilayer superposition [ 45 , 46 ]. Through delignification and impregnation of bamboo sheets with epoxy resin, five layers of transparent bamboo (less than 1.5 mm) achieved a transmittance of 63%.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic structure of TW leads to its anisotropy in optical properties. In order to evaluate the light guiding and directional scattering effects of TW materials, the glass, NW, and TW-3 samples were vertically irradiated by a green laser beam with a diameter of 2 mm. The laser beam passes through the glass without scattering (Figure e), whereas the NW sample blocks the light transmittance (Figure f). In contrast, the laser beam obviously passes through the TW-3 sample.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the cell walls of FW-A and FW-C become thinner as a whole, and there are obvious pores in the intercellular layer and the middle layer of the secondary wall S 2 . This corresponds to the calculation of the above three major elements, indicating that part of the lignin in the wood has been removed, but the overall structure has not been destroyed Figures g and h, respectively, present the local characteristics of TW-AC and TW-ACC.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to the calculation of the above three major elements, indicating that part of the lignin in the wood has been removed, but the overall structure has not been destroyed. 20 Figures 5 g and 6 h, respectively, present the local characteristics of TW-AC and TW-ACC. The above illustrates that the resin PMMA fully impregnates and fills the wood tracheid and parts lacking lignin.…”
Section: Resultsmentioning
confidence: 99%